2017
DOI: 10.1128/jb.00861-16
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Mechanistic Analyses of the Periplasmic Domain of the Enterohemorrhagic Escherichia coli QseC Histidine Sensor Kinase

Abstract: The histidine sensor kinase (HK) QseC senses autoinducer 3 (AI-3) and the adrenergic hormones epinephrine and norepinephrine. Upon sensing these signals, QseC acts through three response regulators (RRs) to regulate the expression of virulence genes in enterohemorrhagic Escherichia coli (EHEC). The QseB, QseF, and KdpE RRs that are phosphorylated by QseC constitute a tripartite signaling cascade having different and overlapping targets, including flagella and motility, the type three secretion system encoded b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 57 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…In contrast, the cooperating TCSs QseCB and QseEF sense and respond to the microbiota-derived quorum sensing molecule AI-3 and the host hormones adrenaline and noradrenaline to activate the transcription of the LEE genes (68,76,77) and allow colonization (78). Following autophosphorylation, QseC activates three RRs, namely, QseB (QseC's cognate RR), QseF, and KdpE (68), via a conserved 8-amino-acid motif in its periplasmic sensing domain (79). QseF is also phosphorylated by its cognate membrane-bound histidine kinase QseE (77).…”
Section: Regulation Of the Lee By Bacterial Two-component Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the cooperating TCSs QseCB and QseEF sense and respond to the microbiota-derived quorum sensing molecule AI-3 and the host hormones adrenaline and noradrenaline to activate the transcription of the LEE genes (68,76,77) and allow colonization (78). Following autophosphorylation, QseC activates three RRs, namely, QseB (QseC's cognate RR), QseF, and KdpE (68), via a conserved 8-amino-acid motif in its periplasmic sensing domain (79). QseF is also phosphorylated by its cognate membrane-bound histidine kinase QseE (77).…”
Section: Regulation Of the Lee By Bacterial Two-component Systemsmentioning
confidence: 99%
“…QseB indirectly represses LEE4 and LEE5 via the sRNA GlmY while activating flagellar and motility genes (24,68,80). QseF promotes the expression of the Shiga toxin (68,79) and the T3SS effector TccP/EspF U , which is necessary for AE lesion formation in EHEC (81). Importantly, QseB (directly) and QseF (indirectly) also repress the FusKR TCS, alleviating fucose-mediated repression and thus shifting the regulatory balance toward the expression of the entire LEE (69).…”
Section: Regulation Of the Lee By Bacterial Two-component Systemsmentioning
confidence: 99%
“…The mutants also differed in their abilities to phosphorylate QseB, KdpE, and QseF. It was concluded that the mutations influenced the phosphotransfer preference of QseC (53).…”
mentioning
confidence: 98%
“…Site-directed mutagenesis of the QseC periplasmic sensing domain yielded four mutants that all exhibited increased levels of phosphorylation but differed in their motility, LEE, and Shiga toxin expression phenotypes (53). The mutants also differed in their abilities to phosphorylate QseB, KdpE, and QseF.…”
mentioning
confidence: 99%
“…The QseBC two-component system (TCS) is found in Proteobacteria, including animal and plant pathogens (57,102,103). The QseC histidine sensor kinase increases its autophosphorylation in the presence of AI-3-Epi/NE molecules and relays this information to its cognate RR QseB and two noncognate RRs, QseF and KdpE (Fig.…”
Section: The Qsebc and Qseef Tcssmentioning
confidence: 99%